The Liver-Protective Effects of the Essential Oil from Amomum villosum in Tilapia (Oreochromis niloticus): Antioxidant, Transcriptomic, and Metabolomic Modulations - Hongbiao Dong; Xiangbing Zeng; Xiaoting Zheng; Chenghui Li; Junchao Ming; Jiasong Zhang (MDPI AG, 2024)
This study investigates the effects of the essential oil from Amomum villosum (EOA) on liver-protective effects in Nile tilapia (Oreochromis niloticus), utilizing a multidisciplinary approach that integrates physiological assessments and transcriptomic and metabolomic analyses. Fish were fed diets containing 2 g/kg of EOA over a 56-day trial, with a no-EOA diet serving as the control. The results demonstrate that EOA supplementation improves liver histology, enhances antioxidant capacities, and reduces inflammation in tilapia. The transcriptomic analysis revealed significant alterations in gene expression profiles related to RNA splicing, metabolism, and disease pathways. The identification of differential genes and disease databases identified key target genes associated with the primary component of EOA for its anti-hepatobiliary disease effects. Furthermore, a molecular docking analysis of EOA major components with core differentially expressed genes in the hepatobiliary syndrome indicated that α-pinene is a potential Hsp90 inhibitor, which may prevent inflammation. A metabolomic analysis further demonstrated that EOA supplementation leads to notable changes in liver phospholipids, fatty acids, and carbohydrate metabolism. These findings underscore the potential of EOA as a natural additive for improving liver health in tilapia, offering valuable insights to the aquaculture industry for enhancing fish health and welfare in intensive farming systems.